IMPLEMENTATION THE EVOLUTIONARY TOURISM TOWARDS GREEN HUMAN RESOURCE MANAGEMENT KENJERAN BEACH SURABAYA CITY - Arif, Mochamad Syaiful; Lukmana, Ardiansyah Hendra; Sodikin, Mohammad (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2022)
This study took the locus of research, namely at Kenjeran Beach Surabaya City, the choice of location was caused by researchers observing that tourism has not been optimal, which is actually potentially very wide tourism area. The formulation of this research problem includes three things, namely: 1) How is the implementation of green human resource management in Kenjeran Beach Surabaya City? 2) What is the role of the government in increasing tourism in the city of Surabaya? 3) What is the strategy to implement tourism optimization of Kenjeran Beach Surabaya City? The method of achieving the objectives of this study uses qualitative with the use of the accuracy of empirical study data and literature studies. The results showed increase Kenjeran Beach tourism are: 1) Massive improvement of soft skills of traders according to the needs of each trader; 2) Continuous evaluation of environmental mainstreaming after a major event was held at Kenjeran Beach in Surabaya City; 3) Establish a special institution for the improvement of soft skills of traders; and 4) Strive to build a PPP system with the private sector in the context of accelerating the increase in tourism of Kenjeran Beach Surabaya City.Â Keywords: Green HRM; Implementation; Tourism